Effects of Folic Acid and Zinc Oxide on Nursery Pig Growth Performance - Larissa L. Becker; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Joel M. DeRouchey; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 360 barrows (DNA 600 × 241; initially 12.1 ± 0.07 lb) were used in a 38-d growth study to evaluate the effects of including folic acid (Rovimix Folic Acid, DSM, Parsippany, NJ) with or without pharmacological levels of Zn provided by zinc oxide (ZnO) on growth performance and fecal characteristics in nursery pigs. Pigs were weaned at approximately 19 d of age and randomly allotted to 1 of 6 dietary treatments. A total of 72 pens were used with 5 pigs per pen and 12 replications per treatment. Dietary treatments were arranged in a 3 × 2 factorial with main effects of folic acid (0, 20, or 40 ppm) and ZnO (3,000 ppm of Zn in phase 1, 2,000 ppm in phase 2, or no Zn other than 110 ppm from the trace mineral premix). Diets were corn-soybean meal-based and fed in 2 phases. A common phase 3 diet was fed to all pigs. For the experimental period (d 0 to 24), pigs fed diets with pharmacological levels of Zn had improved (P£ 0.030) d 24 BW, ADG, and ADFI. There was a quadratic (P<0.05) response for d 24 BW, ADG, and ADFI when pigs were fed folic acid with pigs fed 0 or 40 ppm having improved performance compared with pigs fed 20 ppm. For the common period (d 24 to 38), pigs previously fed pharmacological levels of Zn had poorer (P= 0.028) feed efficiency compared to pigs previously fed diets without pharmacological Zn. Additionally, a quadratic (P= 0.008) response was observed in ADG and ADFI when pigs were previously fed folic acid with pigs fed 0 or 40 ppm having improved performance compared with pigs fed 20 ppm. Overall (d 0 to 38), there was a quadratic (P<0.05) response in final BW, ADG, and ADFI when pigs were fed folic acid, with pigs fed 0 or 40 ppm having improved performance compared to pigs fed 20 ppm. However, no overall differences (P>0.10) were observed when pigs were fed diets with or without pharmacological levels of Zn in phase 1 and 2 diets. Additionally, no statistical differences (P>0.10) in mortality were observed when pigs were fed diets with or without pharmacological levels of Zn although pigs fed no folic acid had numerically the lowest mortality. In conclusion, the addition of folic acid did not improve nursery pig performance with a negative response observed at 20 ppm, regardless of Zn inclusion in the diet.
Keywords: folic acid; zinc oxide; nursery pig